Advances in Plant Breeding Strategies: Agronomic, Abiotic and Biotic Stress Traits - Al-Khayri, Jameel M.; Jain, Shri Mohan; Johnson, Dennis V. (Springer International Publishing : Imprint: Springer, 2016)
Plant breeders and geneticists are under constant pressure to sustain food production by using innovative breeding strategies and introducing minor crops which are well adapted to marginal lands, provide a source of nutrition, and have abiotic and biotic stress tolerance, to feed an ever-increasing human population. The basic concept of this book is to examine the use of innovative methods augmenting traditional plant breeding towards the development of new crop varieties under different environmental conditions to achieve sustainable food production. The book consists of two volumes. This is volume 2 which contains 18 chapters highlighting breeding strategies for specific plant traits including improved nutritional and pharmaceutical properties as well as enhanced tolerance to insects, diseases, drought, salinity and temperature extremes expected under predicted global climate change. Chapters addressing these topics are grouped into four parts: Part I, Sustainability, Nutrition and Pharmaceuticals; Part II, Forage and Tree Traits; Part III, Abiotic Stress Tolerance; and Part IV, Biotic Stress Resistance.  The book is a valuable resource for students, researchers, scientists, commercial producers and seed companies as well as consultants and policymakers interested in agriculture, particularly in modern breeding technologies.